An innovation study on chloride and oxygen diffusions in simulated interfacial transition zone of cementitious material. (July 2020) - Fu, Chuanqing; Ling, Yifeng; Wang, Kejin
Abstract: This study simulated interfacial transition zone (ITZ) by controlling aggregate in type, size, shape, amount and placement to experimentally investigate diffusion coefficients in ITZ in comparison of mortar using an accelerated chloride diffusion test and a newly developed oxygen diffusion test. The water-to- cement ratios (w/c) of 0.55, 0.50, 0.45, 0.40 and 0.35 were used to evaluate w/c effect on diffusion. The results indicated that the simulated ITZ was successfully used to investigate the effect of w/c on chloride and oxygen diffusion properties in ITZ. The diffusion coefficient in ITZ was much larger than that in mortar. An inflexion of diffusion coefficient in ITZ was found with w/c reducing. A critical index M (ratio of DITZ and Dmor ) was used to determine whether the porosity or the ratio of ITZ porosity and mortar porosity dominated diffusion coefficient in ITZ. The relationship between effective diffusion coefficient (overall diffusion coefficient) and M was proposed. Additionally, oxygen diffusion coefficient was much higher than chloride diffusion coefficient.